2008
DOI: 10.1007/s10195-008-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of femoral head osteonecrosis after rotational acetabular osteotomy

Abstract: The natural history of osteonecrosis of the femoral head is generally thought to be one of progressive deterioration if no intervention is undertaken. However, it is unknown whether surgical intervention is beneficial for patients with a small region of osteonecrosis. We observed rapid improvement of MRI findings after rotational acetabular osteotomy (RAO) was performed in a young patient with osteonecrosis of the femoral head. The band-like low signal area on T2-weighted images almost resolved by six months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Individual clinical series have reported varying degrees of success with these procedures (e.g. Nozawa et al, 2008; Berend et al, 2003), and there is no consensus as to which treatments work best. This controversy is due, in part, to the lack of ability to systematically compare treatments in an animal model whose natural history is progression to human-like femoral head collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Individual clinical series have reported varying degrees of success with these procedures (e.g. Nozawa et al, 2008; Berend et al, 2003), and there is no consensus as to which treatments work best. This controversy is due, in part, to the lack of ability to systematically compare treatments in an animal model whose natural history is progression to human-like femoral head collapse.…”
Section: Introductionmentioning
confidence: 99%
“…G enerally, it is believed that ONFH will gradually deteriorate naturally if no intervention is taken. 16,17 Some studies have reported that if no intervention is taken after the first discovery of ONFH signs, some cases of ONFH have improved, and some have neither progression nor tendency to improve; however, most of these cases are for asymptomatic or early ONFH. [18][19][20] Therefore, for symptomatic ONFH seriously affecting the normal functional activities of patients, interventions should be carried out in time, among which hip replacement is currently the most effective and common therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is believed that ONFH will gradually deteriorate naturally if no intervention is taken 16,17 . Some studies have reported that if no intervention is taken after the first discovery of ONFH signs, some cases of ONFH have improved, and some have neither progression nor tendency to improve; however, most of these cases are for asymptomatic or early ONFH 18–20 .…”
Section: Discussionmentioning
confidence: 99%